2012
DOI: 10.1103/physrevb.86.045459
|View full text |Cite
|
Sign up to set email alerts
|

Transition-metal dispersion on carbon-doped boron nitride nanostructures: Applications for high-capacity hydrogen storage

Abstract: Using density-functional theory calculations, we investigated the adsorption of transition-metal (TM) atoms (TM = Sc, Ti, V, Cr, Mn, Fe, Co, and Ni) on carbon doped hexagonal boron nitride (BN) sheet and the corresponding cage (B 12 N 12 ). With carbon substitution of nitrogen, Sc, V, Cr, and Mn atoms were energetically favorable to be dispersed on the BN nanostructures without clustering or the formation of TM dimers, due to the strong binding between TM atoms and substrate, which contains the half-filled lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
32
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 30 publications
1
32
0
Order By: Relevance
“…Unlike the zero-gap semi-metal graphene, BC 3 is a semiconductor with a band gap of 0.46-0.73 eV [38][39][40][41][42][43]. It was shown that the pristine [44], Li-doped [45], polylithiated molecule-doped [46], and transition metal-doped [47][48][49] BC 3 have high potential for H 2 storage.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike the zero-gap semi-metal graphene, BC 3 is a semiconductor with a band gap of 0.46-0.73 eV [38][39][40][41][42][43]. It was shown that the pristine [44], Li-doped [45], polylithiated molecule-doped [46], and transition metal-doped [47][48][49] BC 3 have high potential for H 2 storage.…”
Section: Introductionmentioning
confidence: 99%
“…The H 2 interaction on this medium shows a crossover between Kubas and multipole Coulomb effect depending on the ionic state of AEM and the number of adsorbed H 2 molecules. [25][26][27] For instance, carbon doped boron nitride cages are proven to have promising potential as hydrogen storage materials with a storage capacity of 7.43 wt %. The charge transfer from Be (~ 1.2 e) to nearest carbon atoms (~ 0.4 e to each neighbors) is established to be the cause of the enhanced binding strength.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the simple van der walls dominates the binding of hydrogen molecules to the surface of pure C-based nanomaterials, the surfaces cannot efficiently store hydrogen. However, their metal decorated counterparts such as C 48 B 12 M 12 (M ¼ Fe, Co, Ni) [7], M 32 B 80 (M ¼ Ca and Sc) [8], Rh coated carbon nanotubes [9], metal decorated graphene [10], Li 9 C 60 [11] have exhibited remarkable hydrogen adsorption capacity [12]. Unfortunately, it is difficult to realize these metal decorated materials experimentally, since metal atoms tend to form clusters on the surfaces of nanostructures, and consequently the hydrogen storage capacity drops dramatically.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the binding energy of a metal atom to the substrate should be larger than the experimental cohesive energy of the bulk metal [13]. It was suggested that alkali metals (AM) and alkaline-earth metals (AEM) can produce a homogeneous coating due to their lightweight and low cohesive energies [8,12]. The hydrogen adsorption on these structures has been demonstrated experimentally, such as Li 12 C 60 [13e15].…”
Section: Introductionmentioning
confidence: 99%